Total synthesis of (±)-streptoglyceride A and of putative (±)-streptoglyceride C - Khobragade, Virendra R.; Ramana, Chepuri V. (Organic Letters, 2025)
The first total synthesis of (+/-)-Streptoglyceride A-one of the early members of this family to be isolated-has been accomplished, along with the synthesis of the putative structure of (+/-)-Streptoglyceride C. The unique tricyclic ring present in these natural products has been constructed by employing a gold-catalyzed tandem diynol cycloisomerization followed by one-pot dihydroxylation/trans-glycosylation. The pendant diene unit was fabricated by Takai olefination and subsequent Stille coupling.